ANALISIS TEKNIS DAN EKONOMIS PADA PENGELOLAAN AIR ASAM TAMBANG MENGGUNAKAN KAPUR TOHOR DI KPL 01 AL CIK AYIB PT BUKIT ASAM, Tbk. - Maya Matofani; Lina Rianti; Iranda Septa Pratama (Jurnal Cakrawala Ilmiah, 2025)
This research aims to analyze the management of acid mine drainage (AMD) using quicklime at KPL 01 CIK AYIB PT Bukit Asam, Tbk. from technical and economic perspectives. The research method used is descriptive quantitative with primary data collection through field observations and secondary data from the company. The results show that AMD management at the site uses an active method with the addition of quicklime (CaO) in the first 5 compartments, followed by a passive method using wetlands in the next 9 compartments. The average use of quicklime is 6 sacks (180 kg) per day, capable of neutralizing the pH of AMD from 5.5 to 6.69-8.21 at the outlet. The cost of using quicklime for one month reaches Rp 8,865,000. This study concludes that AMD management using quicklime at the site is technically effective in neutralizing pH according to quality standards and needs further analysis in terms of its economic efficiency.